2008
DOI: 10.1007/s00213-008-1162-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perinatal exposure to delta-9-tetrahydrocannabinol on the emotional reactivity of the offspring: a longitudinal behavioral study in Wistar rats

Abstract: These results suggest that the endocannabinoid system is involved in the control of emotionality since early developmental stages. Thus, even moderate doses of cannabinoid compounds, when administered during the perinatal period, can have profound consequences for brain maturation, leading to long-lasting neurodevelopmental alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 71 publications
9
117
1
4
Order By: Relevance
“…Exposed offspring showed reduced body weight at birth (Abel et al, 1981;Abel et al, 1980). As with humans, young rats exposed to THC throughout pre-and postnatal development had increased ultrasonic vocalizations (cries) when isolated, indicative of increased anxiety and potentially analogous to increased irritability in human infants (Trezza et al, 2008a). In this same study, rats showed deficits in social behaviors during adolescence and elevated anxiety in adulthood.…”
Section: Cannabis/delta-9-tetrahydrocannabinolmentioning
confidence: 78%
“…Exposed offspring showed reduced body weight at birth (Abel et al, 1981;Abel et al, 1980). As with humans, young rats exposed to THC throughout pre-and postnatal development had increased ultrasonic vocalizations (cries) when isolated, indicative of increased anxiety and potentially analogous to increased irritability in human infants (Trezza et al, 2008a). In this same study, rats showed deficits in social behaviors during adolescence and elevated anxiety in adulthood.…”
Section: Cannabis/delta-9-tetrahydrocannabinolmentioning
confidence: 78%
“…An increased retrospective perception of parents neglect in drug users may have been simply influenced by drug-induced psychological and emotional derangement [Rubino and Parolaro, 2008;Trezza et al, 2008]. In fact, SS genotype individuals may have underestimated their parents' care because of drugs effects.…”
Section: Discussionmentioning
confidence: 94%
“…The animals in a pair did not differ more than 10 g in body weight; furthermore, they were housed in different cages and that therefore had no previous common social experience from the arrival in our Facility till the day of testing (File, 1980;Trezza et al, 2008).…”
Section: Behavioral Testsmentioning
confidence: 99%